Colonic epithelial cell mediated suppression of CD4 T cell activation. Issue 5 (13th April 2004) - Cruickshank, S M; McVay, L D; Baumgart, D C; Felsburg, P J; Carding, S R
Abstract : Background and aims: As the first point of contact with enteric antigens, intestinal epithelial cells (IEC) may be key in regulating mucosal immune responses. We determined therefore if murine colonic epithelial cells (CEC) have tolerogenic or activating effects on CD4 T cells. Methods: Using a novel CEC, macrophages, and CD4 T cell coculture system, mitogen and antigen specific responses of naïve and antigen primed CD4 T cells were assessed. Results: Although a proportion of CEC express the costimulatory molecules B7.1, B7.2, CD40, and CD54, they were unable to promote mitogen or antigen driven activation of CD4 T cells, even in the presence of exogenous costimulatory signals. CD4 T cells cocultured with CEC were CD25 lo and CD45RB lo and remained in the G1 phase of the cell cycle. CEC were also able to prevent CD4 T cell activation by professional antigen presenting cells. CEC mediated suppression of T cell activation was cell contact dependent and transforming growth factor β independent. Conclusions: These observations suggest that CEC contribute to the maintenance of T cell tolerance in the gut by preventing inappropriate activation of CD4 T cells.